2007
DOI: 10.1007/s00392-007-0571-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective and non-selective β-blockers on body weight, insulin resistance and leptin concentration in chronic heart failure

Abstract: This study found different metabolic effects of carvedilol and bisoprolol in non-cachectic patients with CHF. With unchanged fasting plasma glucose concentration after 6 months of treatment, carvedilol significantly decreased plasma insulin concentration and insulin resistance compared to bisoprolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 30 publications
0
14
1
4
Order By: Relevance
“…Apart from well established mechanisms such as reduction of sympathetic drive and prevention of arrhythmia [17], other mechanisms should be mentioned [18]. Among other beneficial properties, beta-blockers improve the metabolic profile in terms of insulin sensitivity [19] and substrate utilization [20]. A considerable proportion of patients could have developed cachexia, an irreversible condition with grim outcome [9].…”
Section: Discussionmentioning
confidence: 98%
“…Apart from well established mechanisms such as reduction of sympathetic drive and prevention of arrhythmia [17], other mechanisms should be mentioned [18]. Among other beneficial properties, beta-blockers improve the metabolic profile in terms of insulin sensitivity [19] and substrate utilization [20]. A considerable proportion of patients could have developed cachexia, an irreversible condition with grim outcome [9].…”
Section: Discussionmentioning
confidence: 98%
“…The majority of β-blockers increase insulin resistance, although carvedilol, a combined α-and β-blocker, favorably infl uences myocardial metabolism by reducing FFA uptake [38]. A recent study reported that these benefi cial effects of carvedilol were not seen with bisoprolol, but the study investigated a relatively small number of patients, and further studies are required [39].…”
Section: Conventional Chf Therapymentioning
confidence: 95%
“…Высокая клиническая эффективность небиво-лола при различных сердечно-сосудистых заболе-ваниях -АГ, ИБС, в том числе у больных с СД на сегодняшний день имеет большую доказатель-ную базу -более 70 исследований [30][31][32][33][34][35].…”
Section: российский кардиологический журнал № 4 (102) | 2013unclassified